THE EFFECT OF MASTERING THE LISTENING SKILL ON OTHER SKILLS WHEN TEACHING THE ARABIC LANGUAGE IN UZBEKISTAN (Ustozlar uchun, 2024)
The listening skill is one of the most important skills that the student and learner of the Arabic language must master, as proficiency and mastery of this skill is the best way to teach the Arabic language . The relationship between listening and other linguistic skills is one of interdependence and integration. Listening is the skill that leads to mastering other skills. This skill is extremely important, as this skill is the beginning of the path to mastering other skills. If the student masters the listening skill, he will master the rest of the skills with ease